Achieving Natural Aesthetics in Brow Hair Transplantation: Challenges and Solutions - Kamal Uddin Khan, Farzana Abdullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Eyebrow transplantation has emerged as a reliable solution for eyebrow loss, yet achieving natural aesthetics remains challenging due to the unique anatomical, directional, and density-related factors of brow hair. This study evaluates aesthetic outcomes, patient satisfaction, and the effectiveness of technical innovations in overcoming poor donor density and hair angle discrepancies. Materials and Methods: A prospective study was conducted at Bolan Medical Complex, Quetta, between January 2022 and January 2023. Forty patients with partial or complete eyebrow loss were included. FUE was employed in all cases, with special attention to recipient site design, hair angle, and use of ultra-fine blades and implanters. Patients were evaluated using the FACE-Q scale, Global Aesthetic Improvement Scale (GAIS), and a 5-point satisfaction score at 6 months. Challenges such as poor donor density, improper curl, or low survival rate were documented. Statistical analysis was performed using SPSS v25.0, including paired t-tests and Pearson correlation. Results: The mean satisfaction score was 4.3 ± 0.5. FACE-Q showed high scores in psychosocial impact and satisfaction with appearance (85 ± 7.2). GAIS showed that 77.5% of patients were rated as “much improved” or “very much improved.” Complication rate was low (7.5%), and significant correlation (r = 0.42, p = 0.003) was found between donor density and satisfaction levels. Conclusion: With meticulous technique and aesthetic planning, eyebrow transplantation can yield natural and satisfying results, even in patients with limited donor density. Angled implantation and follicle selection are key to overcoming challenges and optimizing outcomes. Keywords: Eyebrow transplantation, FUE, donor site density, natural aesthetics, brow hair angle, FACE-Q, GAIS